AB0721 OCULAR INVOLVEMENT IN INFLAMMATORY BOWEL DISEASE. STUDY OF 1442 PATIENTS FROM A SINGLE UNIVERSITARY CENTER. (2nd June 2020) - Sanchez-Bilbao, L.; Martinez-Lopez, D.; González-Mazón, I.; García-García, M. J.; Rivero-Tirado, M.; Castro, B.; Crespo, J.; González-Gay, M. A.; Blanco, R.
Abstract : Background: Inflammatory bowel disease (IBD), which includes Crohn's disease (CD), and Ulcerative colitis (UC) are related to Spondyloarthritis (SpA). Ocular manifestations (OM) are well-stablished in SpA but not in IBD. It has been classically reported that whereas uveitis with SpA is predominantly anterior, unilateral, sudden, and limited; in IBD it is bilateral, posterior, insidious, and chronic (Lyons & Rosenbaum JT. Arch Ophthalmol 1997; 115:61-4). Objectives: In a large unselected series of IBD, we study the OM and assess; a ) epidemiological, clinical features, b ) the relationship with extraintestinal manifestations. Methods: Study of all consecutive patients from a single University Hospital during the last 40 years with: a ) IBD (CD and UC), and b ) OM: uveitis and scleral pathology diagnosed by clinical features and slit-lamp. Results: OM were present in 42 (2.9%) (25 women/17 men) (84 eyes) of 1442 IBD patients; OM included the uveitis group (UG) (n=23; 1.6%) and the scleral pathology group (SG) (n=19, 1.32%) (TABLE ). The most common pattern in SG was episcleritis (n=16; 84.21%) and scleritis (n=3). In UG, uveitis was typically anterior (n=18; 78.3%), unilateral (n=19; 82.6%), sudden (n=19; 82.6%), and limited (n=12; 52.2%). The comparative study between SG vs UG showed in UG a significant predominance of women and UC. Also, a non-significative higher frequency in Pyoderma gangrenosum, erythema nodosum and joint involvement was observed in UG. After a mean follow-up of 15.2±9.97 years, extraintestinal manifestations were observed in 100% of patients, being articular forms (n=16; 38.10%) the most common type. In addition, joint/axial flare is more related to the presence of uveitis (p=0.038). Conclusion: Both uveitis and episcleritis are equally frequent OM in IBD. Although uveitis is more infrequent in IBD than in SpA, it is also anterior, unilateral, sudden and limited in contrast with published data from selected series. References: [1]Lyons & Rosenbaum JT. Arch Ophthalmol 1997; 115:61-4 Disclosure of Interests: Lara Sanchez-Bilbao Grant/research support from: Pfizer, David Martinez-Lopez: None declared, Iñigo González-Mazón: None declared, María José García-García: None declared, Montserrat Rivero-Tirado: None declared, Beatriz Castro: None declared, Javier Crespo: None declared, Miguel A González-Gay Grant/research support from: Pfizer, Abbvie, MSD, Speakers bureau: Pfizer, Abbvie, MSD, Ricardo Blanco Grant/research support from: AbbVie, MSD, and Roche, Speakers bureau: AbbVie, Pfizer, Roche, Bristol-Myers, Janssen, and MSD